Why is Pollution from U.S. Manufacturing Declining? The Roles of Trade, Regulation, Productivity, and Preferences - Joseph S. Shapiro; Reed Walker (Institute for the Study of Labor (IZA), 2015)
Between 1990 and 2008, emissions of the most common air pollutants from U.S. manufacturing fell by 60 percent, even as real U.S. manufacturing output grew substantially. This paper develops a quantitative model to explain how changes in trade, environmental regulation, productivity, and consumer preferences have contributed to these reductions in pollution emissions. We estimate the model's key parameters using administrative data on plant-level production and pollution decisions. We then combine these estimates with detailed historical data to provide a model-driven decomposition of the causes of the observed pollution changes. Finally, we compare the model-driven decomposition to a statistical decomposition. The model and data suggest three findings. First, the fall in pollution emissions is due to decreasing pollution per unit output within narrowly defined products, rather than to changes in the types of products produced or changes to the total quantity of manufacturing output. Second, the implicit pollution tax that rationalizes firm production and abatement behavior more than doubled between 1990 and 2008. Third, environmental regulation explains 75 percent or more of the observed reduction in pollution emissions from manufacturing.
Keywords: F18; F64; H23; Q56; 330; environmental regulation; air quality; trade and environment